2021
DOI: 10.17219/acem/138327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amantadine and topiramate on neuronal damage in rats with experimental cerebral ischemia-reperfusion

Abstract: Background. Ischemia-reperfusion models are used to evaluate treatment options that may minimize cellular damage after ischemia.Objectives. To investigate the effects of amantadine and topiramate on apoptosis and cellular oxidative damage. Materials and methods.This experiment was performed using 30 male Wistar albino rats. The right internal carotid artery was identified and clamped with an aneurysm clip under general anesthesia, except for animals in the control group. After 10 min of occlusion, the aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…37 Previous study suggests that amantadine and topiramate can improve I/R injury by reducing apoptosis. 38 We found that the protein accumulation of cleaved caspase-3, cleaved PARP and BAX was enhanced in ODG/R-induced neurons, while BHLHE40 overexpression reduced the protein amount, indicating that BHLHE40 exerted an anti-apoptotic role in I/R injury.…”
Section: Discussionmentioning
confidence: 71%
“…37 Previous study suggests that amantadine and topiramate can improve I/R injury by reducing apoptosis. 38 We found that the protein accumulation of cleaved caspase-3, cleaved PARP and BAX was enhanced in ODG/R-induced neurons, while BHLHE40 overexpression reduced the protein amount, indicating that BHLHE40 exerted an anti-apoptotic role in I/R injury.…”
Section: Discussionmentioning
confidence: 71%
“…76 Furthermore, previous studies conducted on rats have demonstrated the antiapoptotic activity of TPM against methylphenidate-induced neurotoxicity and cerebral ischemia/reperfusion neuronal damage. 18,77 However, the effect of TPM on preventing apoptosis in cardiotoxicity models is still understudied and requires further investigation, including the assessment of other apoptotic and anti-apoptotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, several studies have suggested that TPM possesses antioxidant, anti-inflammatory, and antiapoptotic properties, making it a potential protective agent against diseases characterized by inflammation and oxidative stress. 18,19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation